USE OF AI ENABLED SOFTWARE IN INDIA FOR HIRING. THE NEED FOR LAWS AND COMPREHENSIVE FRAMEWORK FOR HIRING THROUGH AI. - Basu, Nibedita; Dave, Rhishikesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this era the result of what seems to be a lengthy hiring process consisting of screening, conducting numerous interviews and performing background checks, AI tools like Applicant Tracking Systems (ATS) have come into play as a tool to filter resumes based on key standards. This can now be achieved at the stroke of a few minutes, scanning thousands of resumes in accordance with the candidates skills, experiences and best matching keywords. This AI innovation enables quicker responds to be provided to candidates while simultaneously allowing companies to fill open positions at a faster rate than before. Hiring managers and employees are naturally swayed to look favorably towards a particular candidate due to biases that stem from hiring habits, but AI has proven to effectively neutralize this element by analyzing objective factors like skills and qualifications while filtering the demographic data. Specialized machine learning algorithms devised to disregard gender, ethnicity and age serve to strengthen diversity within the AI workforce. Through the utilization of chatbots and virtual assistants, candidates can now receive instantaneous responses to any questions they might have, alongside receiving feedback, enhancing engagement. AI chatbots employ predictive analytics in gauging the prospective success rate of candidates in accordance with previous job performances. By evaluating certain personality traits and overall business culture, the potential turnover rate is reduced, while long-term hires are ensured. By basing the AI-powered personalized job recommendations on candidate profiles, the overall job searching experience is improved which increases the chances of landing the right job.The scholar in this research article has tried to analyse the pros and cons of the hiring process through AI and the benefit that companies would derive out of this boon and the laws and regulations that should be in place to regulate such type of hiring.As we move into the future, there is no doubt AI technology will continue to develop, thus broadly enhancing its features within the workforce.